Pengaruh Aplikasi Youtube Terhadap Kemampuan Komunikasi Anak Di PAUD Al-Ikhlas Desa Aektinga Kecamatan Sosa - Ikhlima Julia Ningsih; Mira Yanti Lubis; Silfa Hafizah Pulungan (Institut Nalanda, 2024)
The aim of this research is to determine: (1) The communication abilities of early childhood in PAUD Al-Ikhlas, Aektinga Village, Sosa District before being given media in the form of the YouTube application, (2) The communication abilities of early childhood in PAUD Al-Ikhlas, Aektinga Village, Sosa District after given media in the form of a YouTube application. This research uses a quantitative approach with an experimental type of research. The research design used pre-experimental with a one group pretest-posttest design type. The instruments used consist of observation, documentation and tests. The data analysis technique uses descriptive statistics and carries out prerequisite tests, namely the normality test and homogeneity test. Test the hypothesis using the